Seismic Properties of Moment-resisting Timber Joints with a Combination of Bolts and Nails - Awaludin A.; Hayashikawa T.; Oikawa A.; Hirai T.; Sasaki Y.; Leijten A.J.M. (Civil Engineering Dimension, 2011)
Improvement of cyclic or dynamic performance of timber connections has been intensively conducted since the overall response of wooden structures is merely a function of joint performance. For a bolted joint, filling the lead-hole clearance with epoxy resin or gluing high embedding-strength materials at the interface of the individual timber member are probably the most common methods. This study presents cyclic test results of moment-resisting joints with a combination of bolts and nails. The nails were placed closer to the joint centroid than the bolts, acting as additional fasteners and were expected to improve the seismic performance of the joints. Static-cyclic test results confirmed the increase of joint stiffness and moment resistance due to the additional nails. The nails contribute to the increase of hysteretic damping significantly though pinching behavior or narrowing the hysteresis loops close to zero rotation points was still observed. The results indicated that contribution of nails or bolts on moment resistance and hysteretic damping can be superimposed.